2017
DOI: 10.1017/jog.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Subglacial flood path development during a rapidly rising jökulhlaup from the western Skaftá cauldron, Vatnajökull, Iceland

Abstract: ABSTRACT. Discharge and water temperature measurements in the Skaftá river and measurements of the lowering of the ice over the subglacial lake at the western Skaftá cauldron, Vatnajökull, Iceland, were made during a rapidly rising glacial outburst flood (jökulhlaup) in September 2006. Outflow from the lake, flood discharge at the glacier terminus and the transient subglacial volume of floodwater during the jökulhlaup are derived from these data. The 40 km long initial subglacial path of the jökulhlaup was mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 47 publications
(114 reference statements)
3
25
0
Order By: Relevance
“…Recent research has identified that, like other rapidly-rising floods, some of the floods in Skaftá cannot be explained by Nye's (1976) jökulhlaup theory and instead the passage of a subglacial pressure wave forms the initial flood path (Einarsson et al, 2016a(Einarsson et al, , 2016b. This assertion supports other work on rapidly rising jökulhlaups, which have been identified in Iceland and elsewhere (e.g.…”
Section: Volcanically-generated Jökulhlaups In Icelandsupporting
confidence: 77%
“…Recent research has identified that, like other rapidly-rising floods, some of the floods in Skaftá cannot be explained by Nye's (1976) jökulhlaup theory and instead the passage of a subglacial pressure wave forms the initial flood path (Einarsson et al, 2016a(Einarsson et al, , 2016b. This assertion supports other work on rapidly rising jökulhlaups, which have been identified in Iceland and elsewhere (e.g.…”
Section: Volcanically-generated Jökulhlaups In Icelandsupporting
confidence: 77%
“…At moderate elevations in our study area, this hypothesis appears to be inconsistent with late‐season ice deceleration that is generally associated with subglacial channelization because while ice velocity at these elevations begins to fall following the lake drainage event on day ~188, basal uplift continues to increase (Figures b–c; Bartholomew et al, ; Chandler et al, ; Hoffman et al, ). However, supraglacial drainage events, like fast‐rising jökulhlaups, are generally thought to occur so rapidly that subglacial channels cannot effectively develop in the vicinity of lake drainages and subglacial water flows as a turbulent sheet (Dow et al, ; Einarsson et al, ; Flowers et al, ; Werder & Funk, ). Increased subglacial efficiency, however, need not be confined to channelization alone (e.g., Andrews et al, ; Hoffman & Price, ; Meierbachtol et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several following reports showed that rapidly-rising jökulhlaups are often observed (e.g. Einarsson and others, 2016, 2017), and can also occur in non-volcanic environments outside of Iceland (e.g. Grinsted and others, 2017).…”
Section: Introductionmentioning
confidence: 98%